Autophagy mediates hepatic GRK2 degradation to facilitate glucagon‐induced metabolic adaptation to fasting. Issue 1 (22nd November 2019) - Cruces‐Sande, Marta; Arcones, Alba C.; Vila‐Bedmar, Rocío; Val‐Blasco, Almudena; Sharabi, Kfir; Díaz‐Rodríguez, Daniel; Puigserver, Pere; Mayor, Federico; Murga, Cristina
Abstract: The liver plays a key role during fasting to maintain energy homeostasis and euglycemia via metabolic processes mainly orchestrated by the insulin/glucagon ratio. We report here that fasting or calorie restriction protocols in C57BL6 mice promote a marked decrease in the hepatic protein levels of G protein‐coupled receptor kinase 2 (GRK2), an important negative modulator of both G protein‐coupled receptors (GPCRs) and insulin signaling. Such downregulation of GRK2 levels is liver‐specific and can be rapidly reversed by refeeding. We find that autophagy, and not the proteasome, represents the main mechanism implicated in fasting‐induced GRK2 degradation in the liver in vivo. Reducing GRK2 levels in murine primary hepatocytes facilitates glucagon‐induced glucose production and enhances the expression of the key gluconeogenic enzyme Pck1 . Conversely, preventing full downregulation of hepatic GRK2 during fasting using adenovirus‐driven overexpression of this kinase in the liver leads to glycogen accumulation, decreased glycemia, and hampered glucagon‐induced gluconeogenesis, thus preventing a proper and complete adaptation to nutrient deprivation. Overall, our data indicate that physiological fasting‐induced downregulation of GRK2 in the liver is key for allowing complete glucagon‐mediated responses and efficient metabolic adaptation to fasting in vivo.